PENINGKATAN KEMAMPUAN MEMBACA HURUF HIJAIYAH DENGAN MENGGUNAKAN MEDIA KARTU PADA ANAK KELOMPOK A TK MUSLIMAT NU 43 MALANG - Rina Husnul Qotimah; Khoirul Asfiyak; Yorita Febry Lismanda (Jurnal Dewantara, 2020)
The ability to read is not only the activity of sounding the letters, but also gives meaning to the writing that is read, so that children will be able to think about what is read. Learning to read in children must always depart from the context and use of language that can be easily accepted by and not just provide words without context and understanding. In this case teaching reading to children should not only teach letters or words, but also be accompanied by something that can represent words that are read by children. From the results of observations at TK Muslimat NU 43 Malang in Group A children the ability to read hijaiyah letters is still very low so researchers try to apply reading hijaiyah letters by using a media card to be able to improve the reading skills of Group A children's hijaiyah letters with a pleasant atmosphere and not make children not get bored quickly. This type of research is Classroom Action Research. Data sources used are primary and secondary data. Data collection through observation, interviews, documentation.The implementation of Cycle I was carried out during a meeting on Monday, January 13, 2020. The material to be taught was to understand the original form of hijaiyah letters. The implementation of Cycle II was conducted on Monday, January 20. The material taught was to understand the Hijiayah letters and how to read them. The main objective This research is to improve children's abilities to read hijaiyah letters. Group A Muslimat NU 43 Kindergarden as weel as to increase teacher skills in choosing and using appropriate methods and media in the learning process